Long term effect of dune fixation by three shrub species on vegetation and Orthoptera communities in arid dunes of Algeria - Bent El Hadi Sba; Imene Djemai; Daniel Petit; Atika Guendouz Benrima (Journal of Orthoptera Research)
The present work analyzed flora and Orthoptera communities in three different plantations in the arid area of El Mesrane, Djelfa Wilaya, Algeria that begun 31 years earlier as means of fixation. The plantations consisted of retam (Retama raetam (Forssk.) Webb), tamarix (Tamarix gallica L.) and prickly pear cactus or opuntia (Opuntia ficus-indica (L.) Miller). Samplings performed in 2014 recorded 46 plant species and 32 Orthoptera species of which members of the Acrididae family were dominant. Community indices showed a decreasing gradient for both flora and Orthoptera from the retam to the opuntia to the tamarix plantation. Likewise, a growing proportion of plants were linked to mobile sands in the same gradient. The retam plantation having the highest flora diversity is mainly due to the therophytes of European open tufts and plants belonging to perennial xerophile fallow lands. The rarest species of grasshoppers are mainly present in the retam plantation, in contrast to the tamarix plantation where half of the characteristic species are among the most common, suggesting that specialist and generalist species are not distributed randomly but rather to the stability of the habitat.